An automatic tool for reconstructing monthly time-series of hydro-climatic variables at ungauged basins. (September 2017) - Pumo, D.; Lo Conti, F.; Viola, F.; Noto, L.V.
Abstract: Integrative information models for filling/reconstructing hydro-climatic time-series are required for a variety of practical applications. A GIS-based model for a rapid and reliable assessment of monthly time-series of several key hydro-climatic variables at the basin scale, is here developed as plug-in and applied to the entire region of Sicily (Italy). The plug-in, once the desired basin outlet section and time-window are selected, uses appropriate spatial techniques and algorithms to identify its drainage area and estimate the corresponding mean areal rainfall and temperatures time-series. A recent regional regressive rainfall-runoff model is successively applied for the assessment of the runoff time-series. Finally, a consolidated temperature-based method is applied to estimate monthly potential evapotranspiration time-series, while, actual evapotranspiration and soil moisture storage time-series are derived through a classical water balance model. The tool, supported by a preliminarily developed database, includes automatic procedures for data retrieving and processing and a user friendly interface. Highlights: TriMoTiS is a QGiS plug-in for the reconstruction of key hydroclimatic time-series. It provides rapid and reliable mean monthly estimates at any basin of a region. Tests show high model accuracy in both rainfall and runoff assessment. Estimates of evapotranspiration by TriMoTiS are coherent with MODIS estimates. Water balance on secular simulations shows a satisfactory closure.